The Effectiveness of the Mind Mapping Model Through Canva Application for Students’ Recount Text at SMKN 1 Kediri - Legowo, Grace Ajar; Riwayatningsih, Rika; Sulistyani (Proceeding International Conference on Education, 2025)
This study explores the effectiveness of integrating the Mind Mapping model through the Canva application in improving students’ recount text writing skills at SMKN 1 Kediri. Writing recount texts plays a vital role in language learning, as it enables students to narrate personal experiences in a structured and chronological way. However, many vocational students struggle with limited vocabulary, poor text organization, and low confidence in writing. To address these issues, this research employed a quasi-experimental design using pre-test and post-test methods in two eleventh-grade classes. One class was taught recount writing using manual mind mapping, while the other applied Canva-based digital mind mapping. Students’ works were assessed using the COVLM rubric (Content, Organization, Vocabulary, Language, and Mechanics), and the data were analyzed through t-tests and N-Gain. The findings indicate that although both groups improved, the Canva-based group showed significantly higher gains in organization, engagement, and writing quality. Students also demonstrated greater enthusiasm and confidence when using digital tools. The study concludes that Canva-based mind mapping is more effective than manual techniques in enhancing recount writing skills and can serve as an innovative strategy for EFL classrooms.